Isolation and Characterization of Flavonoid from Mimosa pudica - Muhamad Afham; Hendra, Rudi; Teruna, Hilwan Yuda (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Indonesia has a rich biodiversity, including the putri malu plant (Mimosa pudica L.) which is known to have secondary metabolites with medicinal potential but has not been fully utilized. The purpose of this work is to isolate and analyze secondary metabolites from M. pudica. The aerial portions were dried and macerated in methanol before being partitioned using n-hexane, dichloromethane, and ethyl acetate solvents. The ethyl acetate extract was separated using liquid vacuum chromatography, then recrystallized and purity tested (KLT, melting point, and HPLC). The chemical structure was characterized using UV-Vis, FTIR, and NMR (1H and 13C) spectroscopy. One of the 17 fractions generated pure yellow crystals with a melting point of 242-244°C and single prominent peak on HPLC. The study revealed that the chemical was quercetin, a flavonoid with a variety of biological functions. This study demonstrates that M. pudica include active flavonoid compounds that can supportaid in the development of herbal medications based on natural ingredients. These findings lay the groundwork for additional research into its bioactivity and pharmacological potential, particularly as an antidiabetic drug and antioxidant.